The Evolution of Technology and Physical Inactivity: The Good, the Bad, and the Way Forward - Woessner, Mary N.; Tacey, Alexander; Levinger-Limor, Ariella; Parker, Alexandra G.; Levinger, Pazit; Levinger, Itamar (Frontiers in Public Health, 2021)
Since the beginning of time people explored and developed new technologies to make their activities of daily living less labor intense, more efficient and, consequently, more sedentary. In addition, technological advances in medicine throughout history have led to a substantial increase in life expectancy. However, the combination of increased sedentary behavior and increased life-expectancy resulted in a sharp increase in overweight and obesity related chronic conditions and illness. Although people may live longer, they are doing so with poorer physical function and a reduced quality of life. In this review we explore how technological advances have influenced people’s sedentary behavior and, through the lens of the affective-reflective theory (ART), we propose a means by which technology could be repurposed to encourage greater engagement in physical activity.